Facebook – selvfremstilling, small talk og social regulering [Facebook: Self representation, small talk, and social regulation] - Sørensen, Anne Scott (MedieKultur: Journal of media and communication research, 2012)
In this paper, I will document the use of Facebook in a Danish context, taking a mediatisation perspective focused on the network sociality in question (Jensen, 2009; Tække, 2010a/b) and the communication (Miller, 2008) of social media. This discussion is based on a qualitative study from 2010, consisting of participants recruited from a survey study. The study explores three dilemmas resulting from network media’s communicative paradox, involving the premises of self-representation, use of status updates, and social regulation. These dilemmas are contextualised by recent theories of genre and speech-acts (Miller, 2004; Butler, 2005) as well as by existing studies of related issues, such as the composition of personal networks (friend lists) and the degree to which personal profiles are open and accessible (privacy). While the study generally confirms recent research in these fields, such research has not previously been documented (or refined) in a Danish context. The paper’s most important contributions, however, consist of its identification of the three communicative dilemmas, its tentative genre classification of the status update, and its discussion of implicit social regulation and ethics, which have not been previously been considered.